LATIHAN "SALAM TRENDI" TERHADAP KEKUATAN OTOT DAN KECEPATAN BERJALAN LANSIA PASKA STROKE DI KOTA DEPOK - Emmelia Ratnawati (Jurnal Kesehatan Karya Husada, 2021)
Stroke in the elderly resulted in limited autonomy. Exercise Salam Trendy consists of deep breathing exercises, stretching, and range of motion is one exercise to reduce limitations. Exercises done at home and individual 2x / week for 4 weeks. This study aimed to identify the effects of exercise "Salam Trendy" against muscle strength and walking speed of elderly post-stroke in Depok. Quasi-Experimental research design using pre and post test design. Total sample of 44 respondents consisting of the treatment group and the control group were selected with consecutive sampling technique. Evaluation studies conducted on the first and fourth week. The results showed that the arm muscle strength (p = 0.042) and legs (p = 0.005); walking speed (p = 0.002) increased significantly after being given a workout. This means that the exercise “Salam Trendy “ affect the increase in muscle strength and walking speed. The study recommends the need for this exercise as one of the interventions of nurse elderly post-stroke in the community. Keyword: Stroke; the elderly; exercise Salam Trendy; muscle strength, walking speed.